The Effectiveness Ministry of Transportation Regulation No. 82 of 2018 Concerning Tool Control and Road Users Safety in Merjosari Village of Maslahah Mursalah Perspective - Nadya Rachmah Sari (Al-Balad: Journal of Constitutional Law, 2019)
Speed ​​limiting device in the form of speed bump is often found on the streets, especially the environmental road. Speed ​​bump specifications that have been regulated in the Minister of Transportation Regulation regarding height, width, slope, and combination lines are yellow, white and black. These rules are made to bring order to the people who make speed bumps that are not according to standards and can harm road users and damage the function of road facilities. The focus of this research is to describe: Effectiveness of making speed bumps in Merjosari Village, and overview of problems in making speed bumps in Merjosari Village. This research uses empirical juridical research type, with sociological juridical approach. Data sources are primary in the form of interviews, secondary in the form of books, laws. This research uses the method of observation, interview or interview, and study of literature or documents. Then processing data using descriptive analysis. The results of this study First, the Effectiveness of the Regulation of the Minister of Transportation No. 82 Year 2018 Concerning Tool Control and Road Users Safety is deemed ineffective. Second, the installation of speed bump tool limiting devices only slightly gives problems and more on harms and dangers. Then the need for public knowledge and counseling provided by the government or related transportation department. And awareness of problems or mutual comfort in the community and road users. Alat pembatas kecepatan berupa speed bump sering kali ditemui di jalan-jalan, terutama jalan lingkungan. Spesifikasi speed bump yang telah diatur dalam Peraturan Menteri Perhubungan mengenai ketinggian, lebar, kelandaian, serta garis kombinasi berwarna kuning, putih dan hitam. Aturan tersebut dibuat guna menertibkan masyarakat yang membuat speed bump yang tidak sesuai standar dan dapat merugikan pengguna jalan maupun merusak fungsi fasilitas jalan. Fokus penelitian ini yaitu mendeskripsikan: Efektivitas pembuatan speed bump di Kelurahan Merjosari. dan tinjauan maslahah mursalah dalam pembuatan speed bump di Kelurahan Merjosari. Penelitian ini menggunakan jenis penelitian yuridis empiris, dengan pendekatan yuridis sosiologis. Sumber data yaitu primer berupa wawancara, sekunder berupa buku-buku, undang-undang. Penelitian ini menggunakan metode observasi, interview atau wawancara, dan telaah pustaka atau dokumen. Kemudian pengolahan data menggunakan diskriptif analisis. Hasil penelitian ini Pertama, Efektivitas Peraturan Menteri Perhubungan Nomor 82 Tahun 2018 Tentang Alat Pengendali dan Pengaman Pengguna Jalan dinilai belum efektif. Kedua, Pembutan pemasangan alat pembatas kecepatan “speed bump” hanya sedikit memberikan maslahah serta lebih banyak pada mudharat dan bahayanya. Maka perlunya pengetahuan masyarakat dan penyuluhan yang diberikan oleh pemerintah ataupun dinas perhubungan yang terkait. Serta kesadaran akan maslahah atau kenyamanan bersama dalam masyarakat maupun pengguna jalan.